First Report on the Coinheritance of α-Thalassemia and a Rare β-Thalassemia Compound Heterozygosity for the IVS-I-I(G>A)/IVS-II-705(T>G) Mutations in a Syrian Family. (2nd January 2019) - Murad, Hossam; Moassas, Faten
Abstract: We describe a proband originating from Al-Quneitra Province, Syria. His hematology data was as follows: Hb A 24.7%, Hb F 71.1%, Hb A2 4.2%. Molecular analysis, based on DNA sequencing of the β-globin gene mutation, showed for the first time a compound heterozygous IVS-I-1 (G>A) ( HBB : c.92+1G>A)/IVS-II-705 (T>G) ( HBB : c.316-146T>G) on the β-globin gene. A reverse hybridization technique revealed that the proband was also an α-thalassemia (α-thal) –α 3.7 (rightward) deletion carrier. Haplotypes analysis for the seven polymorphic restriction sites showed that the compound heterozygous mutations, IVS-I-1/IVS-II-705, were linked to two haplotypes: I [+ – – – – + +] and VI [– + + – – – +], respectively. Our results showed, for the first time, the presence of rare β-thalassemia (β-thal) IVS-II-705 (T>G) mutation associated with IVS-I-1 (G>A). Our findings suggest the presence of these mutations resulted from past migrations.